The right of legitimate defense in contemporary international law - Medon, Ali Omar Moftah; Muhammad Husni, Ahmad (Institut Islam Hadhari, Universiti Kebangsaan Malaysia (UKM), 2012)
This paper addressed the right to legitimate defense in the international law before the appearance of any international regulation. The significance of the research lies in the fact that it is one of the important topics on the international and national levels. Many countries justify their occupations and invasion of other countries by the right to legitimate defense. This becomes incumbent upon us to clarify the meaning of the right to legitimate defense and its restrictions lest a country interprets the right to legitimate defense as to serve its goals. This research also confirms the right of the weak countries to defend themselves in case they are invaded by the powerful countries. This is the research's second objective. To conclude, the research is culminated with following results: the Security Council is controlled by some countries and consequently, it cannot deal with casualties properly. These countries replaced the Security Council in fulfilling its tasks so they shaped facts to match their interests. When they attack other countries, they interpret it as practicing their right to legitimate selfdefense, but when the attacked countries resist act.